Kelainan Jantung Kucing Secara Ultrasonografi Di Rumah Sakit Hewan Pendidikan Institut Pertanian Bogor Dan Klinik Hewan Di Jakarta - Rasyid, Muflih Muhammad; Ulum, Mohamad Fakhrul; Zaenab, Siti; Noviana, Deni (Jurnal Veteriner; Vol 21 No 3 (2020), 2020)
Heart diseases are the main cause of sudden deaths in cats. Those diseases can be diagnosed using ultrasonography. This study aims to investigate the cases of heart diseases of cats diagnosed by ultrasonography (echocardiography) in Veterinary Teaching Hospital, Faculty of Veterinary Medicine, IPB University and My Vets Animal Clinic, Kemang. Total thirty-one patients’ medical record files from veterinary teaching hospitals (eleven files) and clinics (twenty files) in 2013-2017 were indicated to have heart diseases. The datas acquired from patients’ medical records were signalement, B-mode, M-mode and color flow Doppler echocardiography results, and definitive diagnoses from medical records. Echocardiography examination was performed on conscious animals using a microconvex probe with the right parasternal view and left apical view. The heart diseases were divided into two categories, i.e. congenital and acquired, and each category describes age, sex, and race predispositions to heart diseases. In this study, congenital heart diseases found were aortic stenosis and ventricular septal defect. The acquired heart diseases found in this study were hypertrophic cardiomyopathy, endocardiosis, mitral regurgitation, tricuspid regurgitation, and pericarditis. The results of this study stated that acquired heart diseases had the bigger proportion in cats, compared to congenital diseases. The most prevalent heart disease was hypertrophic cardiomyopathy. As a conclusion, male, Persia and 7-12 years old cats are more susceptible to heart diseases.